ANALISIS STABILITAS DINDING PENAHAN TANAH PADA PROYEK PEMBANGUNAN MESS AEK RANGAT KECAMATAN PANGURURAN KABUPATEN SAMOSIR - Ristanti Pohan; Rahmat Dirgantara (Universitas Islam Sumatera Utara, 2026)
This study analyzes the stability of an earth retaining wall in the Aek Rangat Mess construction project in Pangururan District, Samosir Regency, which faces the challenges of hilly topography and landslide risk. Active and passive earth pressures were analyzed using the Rankine and Coulomb methods, and soil bearing capacity was analyzed using the Terzaghi method. Earthquake effects were calculated using the Mononobe-Okabe, Seed-Whitman, and Wood approaches. The results indicate that the planned retaining wall meets safety requirements against sliding, overturning, and soil bearing capacity failure, thus ensuring structural stability. However, it is recommended that future planning consider deeper variations in soil conditions and a dynamic approach to earthquake loads to increase resilience under extreme conditions. This study identifies critical factors affecting retaining wall performance and contributes to the development of safer designs in hilly and earthquake-prone areas.